2020
DOI: 10.1016/j.soildyn.2019.105864
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of dynamic soil-structure interaction effects for tall buildings: A 3D numerical approach

Abstract: Soil-structure interaction (SSI) phenomena are typically studied in the frequency-domain using the substructure approach, involving several simplifications. In this study, SSI effects for a 20-storey building are studied numerically performing time-domain 3D non-linear dynamic analyses, using an elastoplastic nonlinear constitutive model for the soil. Three foundation systems-a relatively shallow, a deeply embedded and a pile foundation-and two soil profiles are investigated and compared. Specifically, relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(16 citation statements)
references
References 33 publications
0
12
0
1
Order By: Relevance
“…Moreover, SSI was founded to have remarkable influences on the distribution way of the shear forces along the superstructures. Scarfone et al (2020) investigated the impacts of SSI on a 20-storey frame-shear wall building using 3D nonlinear dynamic time history analyses. Particularly, three foundation types (shallow foundation, compensated foundation and pile foundation) were evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, SSI was founded to have remarkable influences on the distribution way of the shear forces along the superstructures. Scarfone et al (2020) investigated the impacts of SSI on a 20-storey frame-shear wall building using 3D nonlinear dynamic time history analyses. Particularly, three foundation types (shallow foundation, compensated foundation and pile foundation) were evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…El-Sherbiny et al [32] applied EBs to study the ability of jet-grout columns to stabilize berms in soft soil formations. EBs found also use in the modelling of piles subjected to different modes of loading, namely lateral [33], passive [34,35], and dynamic loading [36]. More recently, use cases suggest the incorporation of EBs to capture the response of tension members, including tunnel front fiberglass reinforcements [37], rock bolts [38], ground anchors [39], and soil nails [40].…”
Section: Introductionmentioning
confidence: 99%
“…Fathi et al [28] investigated the effect of SSI on the out of plane behavior of walls and found that the displacements and acceleration demands significantly changed. Scarfone et al [29] determined that the soft soil layer behaves like a natural damper.…”
Section: Introductionmentioning
confidence: 99%